Unfolding Hidden Narratives: Glimpses of an Ethos of Senses in a Dementia-Care Facility - Wijngaarden, Els van (The Hastings Center report, 2025)
In this essay, I explore the possibility of meaningful communication and genuine connection within dementia-care settings, and particularly among those living with advanced dementia. Drawing on empirical research and informed by the phenomenology of Bernhard Waldenfels, I aim to challenge dominant cultural narratives that reduce dementia-care institutions to places of confinement and loss. I propose an approach that affirms the irreducible otherness of every human being, including persons with dementia. Through case studies and philosophical reflection, I argue that recognizing the strangeness of both the other and the self can open up mutual spaces of encounter. This, in turn, may cultivate an ethos of the senses: a moral attitude rooted in bodily responsiveness, in which all senses are engaged. Such a responsive posture may not only foster more humane and reciprocal relationships within dementia care contexts but also contribute to richer, more nuanced public narratives about what it means to live with dementia.